Time Series and the Derivation of Demand and Supply Curves A Study of Coffee and Tea, 1850-1930 - Gilboy, Elizabeth Waterman (Quarterly Journal of Economics, 1934)
I. Introduction. 667. — II. The history of the coffee industry, 671; a demand curve for coffee, 1875–1918, 675. — III. The tea industry, 678; derivation of curves, 680; their validity, 684. — IV. Conclusion, 685.